A Preseason Training Program With the Nordic Hamstring Exercise Increases Eccentric Knee Flexor Strength and Fascicle Length in Professional Female Soccer Players - Karoline Baptista Vianna; Lívia Gonçalves Rodrigues; Nathalia Trevisol Oliveira; João Breno Ribeiro-Alvares; Bruno Manfredini Baroni (International Journal of Sports Physical Therapy)
# Background Training programs that include the Nordic hamstring exercise (NHE) have been shown to increase eccentric knee flexor strength and biceps femoris fascicle length in male athletes. However, the effect of NHE on female athletes remains unknown.